Targeted metabolite profiling and de novo transcriptome sequencing reveal the key terpene synthase genes in medicinally important plant, Couroupita guianensis Aubl - Thulasiram, Hirekodathakallu V.; Karegaonkar, Shrikant Jagannathrao; Sharma, Poojadevi; Kumar, Ashish; Ramkumar, Sudha; Pandreka, Avinash (Plant Genetic Resources-Characterization and Utilization, 2023)
The Lecythidaceae family tree, Couroupita guianensis Aubl, popularly known as Nagpushpa, is a widely cultivated ornamental tree with several uses in traditional medicine. The tree is revered as highly sacred in Indian traditional culture due to its uniquely shaped, fragrant flowers. Considering the significance, we were prompted to carry out the metabolite and transcriptome analysis of Nagapushpa. The flower, petals, stamen, stem and leaf of C. guianensis were metabolically profiled, and it was discovered that the flower tissue contained the highest terpenoid reservoir. A number of terpenoid pathway transcripts were also found in the flower tissue after transcriptome profiling. KEGG pathway mapping was carried out to correlate transcript sequences with the biosynthesis of different types of terpenes. We were able to clone three full-length terpene synthase gene candidates, i.e. monoterpene ocimene synthase, diterpene ent-kaurene synthase and sesquiterpene farnesene synthase. The transcript expression of selected terpene synthase genes was also verified in flower tissue. These cloned sequences were used for in silico structural investigations and protein function prediction at the level of 3D structure. The data presented in this study provide a comprehensive resource for the metabolic and transcriptomic profiles of C. guianensis. The study paves the way towards the elucidation of terpene biosynthetic pathway in C. guianensis and heterologous production of useful terpenoids in the future.
Keywords: Couroupita guianensis Aubl; flower; Metabolite profiling; terpene synthases; Transcriptomics